The Effect of Facilities, Promotion, and Service Quality on Interest in Revisiting Kedung Ombo Reservoir Tourist Attractions (Case Study of Kedung Ombo Reservoir Tourists) - Saputra, Alfian; Al Husin, Syahri; Widodo, Zandra (ProBisnis : Jurnal Manajemen, 2024)
Repeat visit interest is a reciprocal result of the value that a customer has spent on an object and makes another form of customer satisfaction. This study intends to examine the effect of (1) Facilities, (2) Promotion, (3) Service Quality on Revisit Interest, either partially or simultaneously. This research is quantitative in nature using primary data. To test the quality of the data, validity and reliability tests were carried out. Observation and questionnaire distribution are the techniques used. From a total sample of 68 with the method of determining the sample, namely purposive sampling. The results of the partial influence between (1) Facilities of 0.232, (2) Promotion sig. value of 0.132, (3) Service Quality has a sig. value of 0.098 on Revisit Interest and the value of these three is greater than alpha 0.05 it can be said that the independent variable has no effect on revisit interest. The simultaneous f test of the three independent variables on the dependent variable in the form of a comparison of the calculated f value of 4,222 which is greater than the calculated f value of 2,758 and the sig. value of 0.009 <0.05, it can be concluded that together (simultaneously) the three independent variables can have an effect on Revisit Interest (Y).